Clinically relevant discordances identified after tertiary reassessment of fetuses with isolated congenital diaphragmatic hernia. (25th July 2017) - Done, Elisa; Gucciardo, Leonardo; Van Mieghem, Tim; Devriendt, Koen; Allegaert, Karel; Brady, Paul; Devlieger, Roland; De Catte, Luc; Lewi, Liesbeth; Deprest, Jan
Abstract: Objective: Fetoscopic endoluminal tracheal occlusion (FETO) may improve outcome of severe isolated congenital diaphragmatic hernia (iCDH). We aimed to identify any discrepancy between initial assessment at the referring hospital and the evaluation at the fetal surgery center, and to document parental decisions following counseling for fetal surgery. Design: Single center retrospective study on patients with presumed iCDH either referred for assessment and counseling or referred for fetal surgery. Discordant findings were defined as either a >10% difference in lung size, discordant liver position or associated anomalies. Results: Outcomes from 129 consecutive assessments over 24 months were analyzed. Among fetal surgery referrals, 2% did not have CDH, and 10% had undiagnosed associated anomalies. Liver position was discordant in 7%. Thirty‐three per cent had discordant lung size. Ninety‐four per cent of patients eligible for surgery underwent FETO. In patients referred because of suspicion of CDH, associated anomalies were found in 14%. Fetal liver and lung assessments were discordant in 50% resp. 38%. Of those patients eligible for FETO, 26% requested termination. For three patients, the postnatal course was marked by a genetic or syndromic additional diagnosis. Conclusion: Discordances between initial assessment before referral and evaluation in our institution were frequent, some of them clinically relevant. © 2017 John Wiley & Sons, Ltd.